Le manioc, entre culture alimentaire et filière agro-industrielle - Vernier, Philippe (éditions Quae, 2018)
The cassava-processing industry plays a key role in food safety and in the economies in the Global South, mainly in rural areas but increasingly in cities too. Climate change is expected to play an even greater role in world agriculture. This book brings together all of the available knowledge on cassava and highlights the agronomic and commercial issues surrounding this crop. It presents an overview of cassava production worldwide, covering all of the various aspects of the plant (botany, genetics), as well as its main forms of cultivation, its diseases and pests. It describes how to use, consume and process cassava.